Alternative Approaches for the Numerical Simulation of Glass Structural Beams Reinforced with GFRP Laminates - Jorge Rocha (Challenging Glass Conference, 2018)
This paper discusses alternative numerical approaches to the analysis of the structural behaviour of glass beams reinforced with GFRP laminates adhesively bonded, which were calibrated and validated from four-point bending tests available in the literature. For this purpose, smeared crack and damaged plasticity models were used to simulate the non-linear behaviour of glass, available in FEMIX and ABAQUS finite element softwares. The interaction between the materials in the composite beams, using polyurethane or epoxy adhesives, was defined thought different strategies. In all cases it was possible to simulate well the non-linear behaviour of glass-GFRP composite beams. However, while the FEMIX (smeared crack model) results showed greater resemblance to the experimental ones, ABAQUS models, showed to be able to capture in greater detail the effects of cracking in theses structural responses.